Diversity and Host Range of Fruit Flies (Diptera: Tephritidae) in Horticultural Commodities in Lembah Seulawah District, Aceh Besar Regency, Aceh Province, Indonesia - Hendrival, Hendrival; Aryani, Dewi Sartika; Saputri, Nanda (Journal of Tropical Horticulture, 2020)
Accurate information on the species and host spectrum is an important aspect of fruit flies management. The study was conducted in August to November 2018 to evaluate the host range and species diversity of fruit flies in Lembah Seulawah District, Aceh Besar Regency, Aceh Province, Indonesia. Fruit flies were collected from 3 villages in Kemukiman Saree: Suka Damai, Suka Mulia, and Saree Aceh. The insects were collected using the trapping method. The modified Lynfield trap baited with methyl eugenol (ME) was used in the research. This modified Lynfield trap was applied using used mineral bottles. Shannon-Wiener diversity index, evenness index, and dominance were applied to determine the diversity of fruit flies. The results revealed that there were six species of fruit flies that acted as pests in 21 species of host plants belonged to 12 families. They were Bactrocera carambolae, Bactrocera latifrons, Bactrocera limbifera, Bactrocera papayae, Bactrocera umbrosa, and Bactrocera verbascifoliae. B. carambolae was found to be dominant insect pest even though the results indicated that diversity and evenness index of fruit flies species in this district were low.